2016
DOI: 10.1088/0953-8984/28/43/434001
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine adsorption on Au(1 1 0): 1D ordering and adaptive reconstruction

Abstract: The adsorption of metal-free phthalocyanine molecules on an anisotropic Au(1 1 0)(1  ×  2) surface has been studied with ultraviolet (UV) photoemission, low-energy electron diffraction and low-temperature scanning tunneling microscopy. In all cases, the molecules form rows in the [1 [Formula: see text] 0] direction, i.e. along the troughs of the reconstructed substrates. However, depending on the exposure and adsorption temperature, the substrate maintains (1  ×  2)- or transforms into a (1  ×  3)-reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…We will refer to this chain structure as "α chain" hereafter. Note that similar chains on the Au(110) terrace have been observed for MnPc [10] and H 2 Pc [22,23] using STM. We found that α CuPc chains are formed preferentially at the step edge.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…We will refer to this chain structure as "α chain" hereafter. Note that similar chains on the Au(110) terrace have been observed for MnPc [10] and H 2 Pc [22,23] using STM. We found that α CuPc chains are formed preferentially at the step edge.…”
Section: Resultssupporting
confidence: 72%
“…Au(110) is typical for such a surface; a clean Au(110) surface displays a (1 × 2) reconstruction, where every second atomic row along ½1 10 lacks and forms a well-patterned trough across the [001] direction (called the "missing row structure") [8]. The adsorption structure of MPc on Au(110)-(1 × 2) has been extensively studied for MnPc [9,10], FePc [11][12][13][14][15][16], CoPc [11,16], CuPc [16][17][18][19][20][21], and H 2 Pc [22,23], mainly by low-energy electron diffraction (LEED) and STM. In the previous study, it has been revealed that MPcs form a well-ordered one-dimensional "chain" structure along the ½1 10 direction on Au(110), which implies that the anisotropy of the substrate has a significant effect on the assembled structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These strong correlations translate into the disappearance of the electron as a fundamental unit, and its replacement by charge and spin collective modes with distinct experimental signatures. These counterintuitive properties should be universal to 1D systems.In this special issue several studies on the structural and electronics properties of various 2D system, namely Pt-induced nanowires on Ge(0 0 1) [1], Pb chains on Si(5 5 3)-Au [2], phthalocyanine molecular chains on Au(1 1 0) [3] and Au-induced nanowires on Ge(0 0 1) [4], are presented. Reference [5] deals with tuning of the directional dependent metal-insulator trans ition in quasi 1D quantum wires with a spin-orbit density wave instability, whereas the lateral electronic screening in quasi-1D plasmons is addressed in reference [6].…”
mentioning
confidence: 99%